Association between dental pain and depression in Korean adults using the Korean National Health and Nutrition Examination Survey. (4th September 2015) - Yang, S. E.; Park, Y. G.; Han, K.; Min, J.A.; Kim, S.Y.
Summary: The purpose of this study was to evaluate the relationships between the prevalence of depression and dental pain using a well characterised, nationally representative, population‐based study. This study analysed data from the 2012 Korea National Health and Nutrition Examination Survey ( n  =   4886). Oral health status was assessed using the oral health questionnaire, and oral examination was performed by trained dentists. Depression was defined as the participant having been diagnosed as depression during the previous year. Logistic regression was applied to estimate adjusted odds ratios (AOR) and 95% confidence intervals (CI), controlling for a range of covariates. Results demonstrated that participants included in 'root canal treatment is necessary' showed higher prevalence of self‐reported dental pain; in particular, participants with depression presented more dental pain than those without depression. After adjusting for sociodemographic factors, self‐reported dental pain increased in participants with depression. The AOR (95% CI) for having self‐reported dental pain was 1·58 (1·08–2·33) in dentists' diagnosis of no dental pain/depression group, 1·62 (1·32–1·98) in dentists' diagnosis of dental pain/no depression group and 2·84 (1·10–7·37) in dentists' diagnosis of dental pain/depression group. It was concluded that depression was associated with dental pain after adjustment for potential confounders in Korean adults. Thus, dentists should consider the possible presence of psychopathology when treating patients with dental pain.